(untitled) (Health Education in Practice: Journal of Research for Professional Learning, 2020)
On behalf of the Health Education in Practice: Journal of Research for Professional Learning editorial team, I would like to extend my sincere thanks to all who have contributed to the journal in 2020. In particular I would like to acknowledge those who contributed as peer reviewers. Your generosity with your time and expertise has been invaluable to the continued high quality of the journal. In short, the Journal cannot function without help from our peer reviewers.